Leucaena leucocephala (Lam.) de Wit as protein supply for heifers (Agro Productividad, 2022)
Objective: To estimate the percentage of Leucaena in the diet of heifers fed with Taiwan grass, in order to maximize the efficiency of the ruminal supply of microbial Nitrogen (ERSMN).Design/Methodology/Approach: Five heifers were randomly selected for each of the five treatments (0, 20, 40, 60, and 80% supplementation with Leucaena), according to a 5×5 Latin square experimental design. We determined the ruminal supply of microbial nitrogen (RSMN), ERSMN, and the urea-N by measuring N and purine derivatives in urine. Subsequently, we predicted the duodenal RSMN, the rumen nitrogen balance (RNB), and the urea cost with the Large Ruminant Nutrition System (LRNS v. 1.0.33) model.Results: The inclusion of Leucaena improved (P≤0.05) the RSMN. The ERSMN estimated by purine derivatives had a quadratic response (P≤0.05) at the inclusion level of Leucaena in the diet. The RNB, the cost of urea, and the urea-N increased (P≤0.05) with a higher inclusion percentage of Leucaena. The maximum ERSMN and N balance were obtained with 20% Leucaena in the ration.Study Limitations/Implications: The expression of the nitrogen utilization potential of Leucaena for microbial protein synthesis in this study was likely restricted by the limited availability of non-fiber carbohydrates (NFC). Further studies must be conducted to determine the most affordable source of NFC to match Leucaena nitrogen utilization in the rumen.Findings/Conclusions: Leucaena could be used as an efficient protein source for heifers at a 20% inclusion in their diet.